Grain Size Distribution of Stabilised Aeolian Dune Sediments in Inner Somogy, Hungary - Györgyövics, Katalin; Kiss, Tímea; Sipos, György (Journal of Environmental Geography, 2014)
In Inner Somogy the former researches concluded that the grain size of stabilised aeolian dunes decreases from north to south fitting to grain size distribution of the alluvial fan the dunes were built of and to the prevailing wind. However, the trend is not so evident, if considering the dune types and sand moving periods. The aim of this paper is to analyse the grain size distribution trends from the point of view of (1) different dune classes, (2) OSL age and (3) general morphological characteristics of the region. During the analysis the grain size distribution of 345 samples from 17 cores (120-300 cm in depth) was determined, and 15 OSL samples were dated. According to the results, the material of simple forms and level 1 dunes (these are the lowest dunes on the surface of the alluvial fan) becomes finer southward, in accordance with the structure of the alluvial fan and prevailing wind direction. Similar trend applies for level 2 dunes (which were formed on the top of level 1 dunes), but it does not apply for level 3 dunes, which are situated on the top of other dunes. It seems that the grain size is inversely proportional to the size of a dune and its age, thus younger and smaller dunes have coarser and less well sorted material. The sediments of the oldest, large parabolic dunes are the finest, younger, medium size parabolic forms have fine material, and the youngest hummocks contain the coarsest sand. The decreasing grain size towards south is the most apparent along longitudinal residual ridges, while within parabolic dunes the wings contain finer material than their elevated head.